Computing Connection-Based Topological Indices of Dendrimers - Aqsa Sattar; Muhammad Javaid; Ebenezer Bonyah (Journal of Chemistry)
Dendrimers are artificially synthesized polymeric macromolecules composed of frequently branching chains called monomers. Topological indices (TIs) are the molecular descriptors which characterize the topology and help to correlate the distinct psychochemical properties such as stability, boiling point, and strain energy of molecular compounds. TIs are classified on the basis of their degrees, distance, and spectrum. Among these TIs, connection-based topological descriptors have great significance. In this study, we initiate the general expressions to compute multiplicative connection Zagreb indices (MZIs), named as first MZCI, second MZCI, third MZCI, fourth MZCI, modified first MZCI, modified second MZCI, and modified third MZCI of two exceptional dendrimers nanostars, namely, poly (propyl) ether imine (PPIE) dendrimer and polypropylenimine octamin (PPIO) dendrimer. Furthermore, in order to check the superiority of our computed results, a comparative analysis is conducted.